2020
DOI: 10.1021/acs.jafc.0c01974
|View full text |Cite|
|
Sign up to set email alerts
|

Herbicidal Characteristics and Structural Identification of the Potential Active Compounds from Streptomyces sp. KRA17-580

Abstract: Weeds are notorious plant species exhibiting a harmful impact on crops. Biological weed control is an efficient and environmentally friendly technique, usually constitutes naturally derived compounds, including bioherbicidal metabolites produced by Streptomyces sp. The isolation and structural identification of phytotoxic compounds from Streptomyces have recently been proposed as an effective way to the discovery of novel bioherbicides. In the screening of bioherbicidal agents, isolated Streptomyces strain KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In total, eleven polyaromatic compounds were isolated from six Streptomyces species in 2020. Through herbicidal bioassay screenings, Kim et al identified strong activity associated with Streptomyces strain KRA17-580 against the weed Digitaria ciliaris [29]. Two compounds were spectroscopically characterised, a cinnoline-4-carboxamide, 580-H1 (38), and a cinnoline-4-carboxylic acid, 580-H2 (39, Figure 13).…”
Section: Polyaromaticsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, eleven polyaromatic compounds were isolated from six Streptomyces species in 2020. Through herbicidal bioassay screenings, Kim et al identified strong activity associated with Streptomyces strain KRA17-580 against the weed Digitaria ciliaris [29]. Two compounds were spectroscopically characterised, a cinnoline-4-carboxamide, 580-H1 (38), and a cinnoline-4-carboxylic acid, 580-H2 (39, Figure 13).…”
Section: Polyaromaticsmentioning
confidence: 99%
“…Two compounds were spectroscopically characterised, a cinnoline-4-carboxamide, 580-H1 ( 38), and a cinnoline-4-carboxylic acid, 580-H2 (39, Figure 13). In further phytotoxicity bioassays, the carboxamide proved to be less potent than the carboxylic acid, and electrolyte leakage assays were used to verify that the observed herbicidal activity was caused by destruction of the cell membrane [29]. 39), (2S,2′′S)-6-lavandulyl-7,4′-dimethoxy-5,2′-dihydroxylflavanone ( 40), (2S,2′′S)-6-lavandulyl-5,7,2′,4′-tetrahydroxylflavanone (41), and (2′′S)-5′-lavandulyl-2′-methoxy-2,4,4′,6′-tetrahydroxylchalcone (42) [29,30].…”
Section: Polyaromaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that the production loss caused by weeds is approximately 34% of the crop yield worldwide (Harding and Raizada, 2015 ; Shi et al, 2020 ). In the present situation, control weeds in farmland on a global scale are mainly dependent on chemical treatments (Travaini et al, 2016 ; Vurro et al, 2018 ); however, there are many long-term problems with the intensive application of agrochemical herbicides, such as environmental pollution, pesticide residue accumulation, and the emergence of weed resistance, which increase the difficulty of weeds control management (Kim et al, 2020 ; Shi et al, 2020 ). With the continuous discoveries of a great number of biocontrol microbial resources, exploration of microbes with excellent biological activity from extreme conditions such as marine-derived microorganisms, in recent years, have attracted much attention of scientists (Shen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%